A polishing disc and its preparation method and application
By inserting and evenly distributing metal nanoparticles in the hot melt material layer of the polishing disk, the problem of damage caused to the surface of the polishing components during the polishing process is solved, and the polishing effect of abrasive-free polishing and sub-anger-level surface roughness is achieved.
Patent Information
- Application Number
- CN202411766230.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Existing polishing discs are prone to damage the surface of polishing components during the polishing process, and it is difficult to achieve sub-Amie-level surface roughness.
A polishing disk with metal nanoparticles embedded in the hot melt material layer is used. The metal nanoparticles are evenly distributed on the polishing surface and partially exposed, and are uniformly distributed through constant magnetic field enrichment.
There is no need to add abrasive particles during the polishing process, avoid damage to the surface of the polished components, and can achieve sub-Amie-level surface roughness.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polishing and grinding, and in particular to a polishing disc and a preparation method and application thereof. Background Art
[0002] The processing method of hard and brittle materials such as optical glass and semiconductor wafers is usually based on chemical mechanical polishing. Under certain load conditions, the polishing disk and the polishing liquid with abrasive particles are subjected to relative friction movement with the workpiece surface, so that the polishing liquid, abrasive particles and the workpiece surface in the polishing interface react chemically. Subsequently, the surface material is removed under the mechanical stress of the hard abrasive particles and is taken away from the friction interface by the polishing liquid, thereby achieving the flattening of the polished surface. This processing process involves the participation of free abrasive particles, and amorphous metamorphic layers are prone to appear on the processed surface. In addition, the abrasive particles cause certain differences in the uniformity of the removal of the entire surface at the microscopic scale, making it difficult to achieve the manufacturing of sub-angstrom surface roughness of large-sized components.
[0003] At present, there are literature reports that by adjusting the material and particle size of free abrasives, as well as the material of the polishing disc, and optimizing the processing technology, the polishing of crystal components can be achieved. In terms of the design of the polishing disc, some literature reports that by mixing fixed abrasives with materials such as asphalt, rosin, and fluff, it can be used for the processing of optical components. In addition, for the polishing of curved optical components, some literature reports that by using a small grinding head, that is, reducing the size of the polishing disc, and further combining slurry containing abrasive particles to achieve the polishing of curved components. In addition, there are also methods such as jets to limit abrasives to specific areas, and use fluids to drive the abrasive particles and the workpiece surface to move relative to each other to achieve polishing. In addition, there are also literature reports that polishing discs made by mixing hard abrasive particles such as aluminum oxide and boron nitride with binders are used to polish the surface of optical components. The material removal process of this method involves the mechanical friction between the abrasive particles and the workpiece. At the microscopic scale, the surface material of the workpiece will be subjected to greater stress, and sub-surface damage at the crystal level will be introduced.
[0004] For chemical mechanical polishing, small grinding head polishing, fixed abrasive polishing and jet polishing, the mechanical action of hard abrasives is involved, and it is difficult to avoid scratches and damage to the amorphous layer on the processed surface, which has a great impact on the corrosion resistance and other properties of the components to be polished. In addition, for the processing form containing free abrasives, it is difficult to control its motion trajectory, and the treatment of waste polishing slurry increases the processing cost. Therefore, the existing technology needs to be improved. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a polishing disc and a preparation method and application thereof, aiming to solve the problem that the existing polishing disc may damage the surface of the component to be polished during the polishing process.
[0006] The technical solution of this application is as follows:
[0007] In a first aspect of the present application, a polishing disc is provided, comprising a hot-melt material layer and metal nanoparticles embedded in the hot-melt material layer, wherein the metal nanoparticles are evenly distributed on a polishing surface of the polishing disc and partially exposed on the polishing surface.
[0008] Preferably, the metal nanoparticles include at least one of a metal element and a metal alloy; the metal element is one of titanium, chromium, iron, cobalt, nickel, molybdenum, palladium, tantalum, and platinum; and the metal alloy is a combination of at least two of titanium, chromium, iron, cobalt, nickel, molybdenum, palladium, tantalum, and platinum.
[0009] Preferably, the metal nanoparticles protrude from the polishing surface, and the height of the metal nanoparticles protruding from the polishing surface is not less than 5% of the particle size of the metal nanoparticles; the sum of the cross-sectional areas of the parts of the metal nanoparticles protruding from the polishing surface at the same height as the polishing surface is not less than 5% of the area of the polishing surface.
[0010] Preferably, the mass ratio of the hot-melt material in the hot-melt material layer to the metal nanoparticles is greater than or equal to 100:1.
[0011] Preferably, the hot-melt material is at least one of asphalt, rubber and silica sol.
[0012] Preferably, when the hot-melt material is asphalt, the needle penetration of the asphalt is 77-80 mm; when the hot-melt material is silica sol, the Shore hardness of the silica sol is 20-40 degrees.
[0013] Preferably, the particle size of the metal nanoparticles is 1 nm-800 μm.
[0014] The second aspect of the present application provides a method for preparing the polishing disc of the first aspect of the present application, comprising the steps of: providing the hot-melt material and the metal nanoparticles; heating the hot-melt material to a molten state, adding the metal nanoparticles, mixing, and obtaining a polishing disc precursor; transferring the polishing disc precursor to a mold, applying a constant magnetic field to a side of the mold away from the outlet, and performing a cooling treatment to obtain the polishing disc; wherein the range of the constant magnetic field is greater than the area of the polishing disc, and the magnetic field strength of the constant magnetic field is not less than 10T.
[0015] The third aspect of the present application provides an application of the polishing disc of the first aspect of the present application in the preparation of optical window components and semiconductor components, wherein the polishing disc is used to polish components used for optical windows and semiconductor components.
[0016] Preferably, the method of using the polishing disk to polish components applied to optical windows and semiconductor components includes: adding polishing liquid to the surface of the components applied to optical windows or semiconductor components to be polished, and using the polishing disk to polish the components applied to optical windows or semiconductor components to be polished; the polishing liquid includes an ionic liquid with a pH value of less than 10.
[0017] Beneficial effects of the present application: The polishing disc of the present application embeds metal nanoparticles in a hot-melt material layer, and the metal nanoparticles are evenly distributed on the polishing surface of the polishing disc and partially exposed on the polishing surface. When the polishing disc polishes the component to be polished, the polishing surface and the component to be polished rub against each other, and the metal nanoparticles promote the hydrolysis of the polishing liquid. The hydroxyl radicals generated by the hydrolysis of the polishing liquid are adsorbed on the polishing surface and the surface of the component to be polished. During the friction process, the hydroxyl groups undergo dehydration condensation to form metal XO-Si chemical bonds on the interface. Under the lateral shearing action caused by the relative movement of the interface, the surface material of the component to be polished is taken away layer by layer and gradually flattened. The polishing disc of the present application does not need to add abrasives during the polishing process, will not damage the surface of the component to be polished, and can achieve polishing of a sub-angstrom level surface roughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for describing the embodiments are briefly introduced below.
[0019] Figure 1 A schematic diagram of the structure of the polishing disc provided in the embodiment of the present application when used for polishing;
[0020] Figure 2 A schematic diagram of a process for preparing a polishing disc provided in an embodiment of the present application;
[0021] Figure 3 Atomic force microscope morphology observation diagram of the optical glass sample before and after polishing provided in the embodiment of the present application;
[0022] Figure 4 Atomic force microscope morphology observation diagram of another optical glass sample before and after polishing provided in an embodiment of the present application;
[0023] Figure 5 An analysis diagram of the polishing effect of the polishing disc prepared in Example 2 on the optical glass sample provided in the application examples;
[0024] Figure 6 This is an analysis chart of the polishing effect of the polishing disc prepared in Comparative Example 2 provided in the embodiments of the present application on the optical glass sample. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings and embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present application. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0026] It should be noted that if there are descriptions involving "first", "second", etc. in the implementation of this application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance and implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the fact that ordinary technicians in the field can implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this application.
[0027] See also Figure 1 The embodiment of the present application provides a polishing disc, comprising a hot-melt material layer and metal nanoparticles embedded in the hot-melt material layer, wherein the metal nanoparticles are evenly distributed on the polishing surface of the polishing disc, and the metal nanoparticles are partially exposed on the polishing surface. The polishing surface refers to the side of the polishing disc that contacts the component to be polished during polishing.
[0028] In some embodiments, the metal nanoparticles include at least one of a metal element and a metal alloy, the metal element is one of titanium, chromium, iron, cobalt, nickel, molybdenum, palladium, tantalum, and platinum, and the metal alloy is a combination of at least two of titanium, chromium, iron, cobalt, nickel, molybdenum, palladium, tantalum, and platinum.
[0029] When a polishing disc is used to polish a component to be polished, the polishing surface contacts and rubs against the component to be polished. Since metal nanoparticles are evenly distributed on the polishing surface of the polishing disc and multiple catalytic reaction sites are formed on the surface of the polishing disc, the hydrolysis of the polishing liquid can be promoted. The hydroxyl radicals generated by the hydrolysis are adsorbed on the polishing surface and the surface of the component to be polished. During the friction process, the hydroxyl groups undergo dehydration condensation to form a bond at the interface (XO-Si chemical bond, where X is a metal). Under the lateral shearing effect caused by the relative movement of the interface, the rough peaks on the surface of the component to be polished first contact the polishing surface and are removed layer by layer under the lateral shearing force, so that the surface of the component to be polished is gradually flattened. At the same time, there is no need to add abrasives during the polishing process, and the components to be polished will not be damaged due to the presence of abrasives.
[0030] In some embodiments, the metal nanoparticles protrude from the polishing surface, and the height of the metal nanoparticles protruding from the polishing surface is not less than 5% of the particle size of the metal nanoparticles; the sum of the cross-sectional areas of the parts of all metal nanoparticles protruding from the polishing surface at the same height as the polishing surface is not less than 5% of the area of the polishing surface. If the exposure degree of the metal nanoparticles is less than the above description, there are fewer catalytic reaction sites between the polishing surface and the component to be polished, and sufficient lateral shearing effect cannot be generated, resulting in poor polishing effect.
[0031] In some embodiments, the mass ratio of the hot-melt material to the metal nanoparticles in the hot-melt material layer is greater than or equal to 100: 1. If the mass ratio of the hot-melt material to the metal nanoparticles is less than 100: 1, the number of metal nanoparticles on the polishing surface is too small, and the catalytic reaction sites formed are also reduced, resulting in a weakened polishing effect.
[0032] In some embodiments, the hot melt material is at least one of asphalt, rubber, and silica sol. Preferably, when the hot melt material is selected as asphalt, the needle penetration of the asphalt used is 77-80mm, for example, the needle penetration of asphalt is 77mm, 78mm, 79mm or 80mm. Asphalt penetration is one of the main quality indicators of asphalt. It is an indicator of the hardness and consistency of asphalt, the ability to resist shear damage, and the relative viscosity of asphalt under certain conditions. At 25°C and 5s, under a load of 100g, the depth of the standard cone penetrating vertically into the asphalt sample is the needle penetration. When the hot melt material is selected as silica sol, the Shore hardness of the silica sol used is 20-40 degrees (HA), for example, the Shore hardness of the silica sol is 20 degrees, 25 degrees, 30 degrees, 35 degrees or 40 degrees. Shore hardness refers to the reading of the value measured by a Shore hardness meter, usually in degrees, and the Shore hardness defined above is described using Shore A as the scale.
[0033] In some embodiments, the particle size of the metal nanoparticles is 1 nm-800 μm. For example, the particle size of the metal nanoparticles is 1 nm, 10 nm, 100 nm, 500 nm, 1 μm, 10 μm, 100 μm, 300 μm, 500 μm or 800 μm, etc. The use of metal nanoparticles of the above particle sizes can play the role of metal particles in promoting hydrolysis, and will not cause scratches due to the high hardness of the particles.
[0034] The present application also provides a method for preparing the polishing disc as described above in the present application embodiment. Figure 2 As shown, the steps include:
[0035] S1. Provide hot-melt material and metal nanoparticles.
[0036] The hot melt material is mainly composed of carbon, hydrogen, oxygen, sulfur, fluorine and sodium. Preferably, the hot melt material is at least one of asphalt, rubber and silica sol. The penetration of asphalt is the same as above, the hardness of rubber is the same as above, the hardness of silica sol, the composition and particle size of metal nanoparticles are the same as above, and will not be described in detail.
[0037] S2. Heat the hot-melt material to a molten state, add metal nanoparticles, mix well, and obtain a polishing disk precursor.
[0038] The specific steps may be: placing a hot melt material in a crucible, placing the crucible on a temperature-controllable heating table for heating to melt the hot melt material, then adding metal nanoparticles and mixing to obtain a polishing disc precursor.
[0039] In some embodiments, the mass ratio of the hot melt material to the metal nanoparticles is greater than or equal to 100: 1. For example, the mass ratio of the hot melt material to the metal nanoparticles is 100: 1, 150: 1, 200: 1, 300: 1 or 500: 1, etc.
[0040] S3, transferring the polishing disc precursor to the mold, applying a constant magnetic field on the side of the mold away from the outlet, and cooling the mold to gradually solidify the polishing disc precursor, and finally making a polishing disc. Under the action of the constant magnetic field, the metal nanoparticles are attracted by the magnetic field to the side close to the magnetic field and enriched. Since the metal nanoparticles in the polishing disc precursor are evenly distributed, under the action of the magnetic field, the metal nanoparticles are also evenly distributed on the polishing surface.
[0041] Among them, the shape of the mold can be set according to actual needs and is not specifically limited. The constant magnetic field can be made of materials or equipment that can generate magnetism, such as permanent magnets or electromagnets. In this process, when the polishing disc precursor is placed in the mold, due to the effect of the magnetic field, the metal nanoparticles in the polishing disc precursor will be attracted to the bottom of the mold by the magnetic field, and during the cooling process, the hot melt material in the polishing disc precursor gradually changes from liquid to solidified. Finally, when it is completely solidified to form a polishing disc, the metal nanoparticles are evenly distributed on one side of the polishing disc (polishing surface); under the joint action of the magnetic field and the mold, the metal nanoparticles will be partially exposed on the polishing surface.
[0042] In some embodiments, the range of the constant magnetic field is larger than the area of the polishing disk, and the magnetic field strength of the constant magnetic field is not less than 10 T. The distance and magnetic field strength of the constant magnetic field can be adjusted according to actual conditions, and the metal nanoparticles can be enriched by the magnetic force of the magnetic field and evenly distributed on the polishing surface.
[0043] In some embodiments, the temperature reduction treatment may be performed by placing the polishing disk precursor at room temperature.
[0044] In some embodiments, the polishing disk precursor prepared in S2 can also be transferred to a polishing base disk and shaped using a specific tool. After the whole is flipped 180 degrees, a constant magnetic field is applied to the side of the mold away from the outlet to enrich the metal nanoparticles, and the temperature is lowered so that the metal nanoparticles are evenly distributed on the polishing surface to obtain a polishing disk.
[0045] The present application also provides an application of the polishing disc described above in the present application to prepare components or semiconductor components for use in optical windows. Components for use in optical windows include planar optical components, curved optical components, etc., and semiconductor components include semiconductor wafers, etc.
[0046] The polishing method using a polishing disk may include the steps of: adding a polishing liquid to the surface of the component to be polished, and polishing the component to be polished using the polishing disk, wherein the polishing liquid is water or an ionic liquid with a pH value less than 10, and the ionic liquid does not contain free abrasive particles. For example, the ionic liquid with a pH value less than 10 may be sodium chloride.
[0047] In some implementations, the component to be polished may be immersed in a polishing liquid, and during polishing, the polishing disk is brought into contact with the component to be polished for polishing.
[0048] For example, when the optical glass is polished using the polishing disc as described above in the embodiment of the present application, the polishing head rotation speed is set to 5-3000 rpm, the polishing head movement speed is set to 50-500 mm / min, the pressure range is 1-1000 hPa, and the polishing liquid is pure water.
[0049] The following is further described by means of specific examples.
[0050] Example 1
[0051] (1) Use a balance to weigh 10 g of solid asphalt particles with a needle penetration of 77 mm and 5 g of molybdenum powder with a particle size of 1 μm. Introduce the solid asphalt particles into a crucible. Place the crucible on a temperature-controlled heating table and heat it until the solid asphalt particles are in a molten state. Add the weighed molybdenum powder and stir evenly. Continue heating to obtain a polishing disk precursor.
[0052] (2) A polishing disc substrate with a diameter of D = 15 mm was selected, and the polishing disc precursor was evenly covered on the polishing disc substrate, and a mold was placed on top to define its surface flatness and shape. After the polishing disc substrate and the mold were inverted (rotated 180 degrees), a permanent magnet (magnetic field strength was not less than 10T) was placed on the mold, and the polishing liquid precursor was waited to cool to room temperature to obtain a polishing head, which included a polishing disc substrate and a polishing disc located on the polishing disc substrate. The height of the metal nanoparticles protruding from the polishing surface in the prepared polishing disc was measured to be 800 nm, and the sum of the cross-sectional areas of the parts of the metal nanoparticles protruding from the polishing surface at the same height as the polishing surface was 8% of the polishing surface area.
[0053] Example 2
[0054] (1) Use a balance to weigh 20 g of solid asphalt particles with a needle penetration of 80 mm and 5 g of molybdenum powder with a particle size of 1 μm. Place the solid asphalt particles into a crucible. Place the crucible on a temperature-controlled heating table and heat until the solid particles are in a molten state. Add the weighed molybdenum powder and stir evenly. Continue heating to obtain a polishing disk precursor.
[0055] (2) A polishing disk substrate with a diameter of D = 15 mm was selected, and a polishing liquid precursor was evenly covered on the polishing disk substrate, and a mold was placed on top to define its surface flatness and shape. After the polishing disk substrate and the mold were inverted (rotated 180 degrees), a permanent magnet (magnetic field strength was not less than 10 T) was placed on the mold, and the polishing liquid precursor was waited for to cool to room temperature to obtain a polishing head, which included a polishing disk substrate and a polishing disk located on the polishing disk substrate. The height of the metal nanoparticles protruding from the polishing surface in the prepared polishing disk was measured to be 600 nm, and the sum of the cross-sectional areas of the parts of the metal nanoparticles protruding from the polishing surface at the same height as the polishing surface was 5.6% of the area of the polishing surface.
[0056] Comparative Example 1
[0057] The preparation method of this comparative example is the same as that of Example 1, except that no molybdenum powder is added.
[0058] Comparative Example 2
[0059] The preparation method of this comparative example is the same as that of Example 2, except that in step (2), the polishing liquid precursor is evenly covered on the polishing disk substrate, and a mold is placed on top to limit its surface flatness and shape, no permanent magnet is placed on top, and the polishing liquid precursor is waited to cool to room temperature to obtain a polishing head, which includes a polishing disk substrate and a polishing disk located on the polishing disk substrate.
[0060] Test Example 1
[0061] The polishing heads prepared in Example 1 and Comparative Example 1 were tested respectively. The polishing head was clamped on the motor, and a 50mm×50mm×10mm optical glass sample was fixedly clamped on the XY motion platform. The position of the XY motion platform was adjusted so that the optical glass sample was immersed in pure water. The motor was controlled to move the polishing head to contact the surface of the optical glass sample, and the polishing head rotated at 100rpm. The XY motion platform traversed the entire optical glass sample at a speed of 50mm / min in the form of a grating motion. The normal load was set to 10N during the process. After polishing, the optical glass sample was removed and the surface morphology of the optical glass sample was observed using an atomic force microscope. Three areas on the surface of the optical glass sample were selected respectively. The morphology differences before and after polishing were as shown in the following results. Figure 3 and Figure 4 As shown, Figure 3 This is a surface morphology observation diagram of an optical glass sample after polishing using the polishing head prepared in Example 1. Figure 4 This is an observation picture of the surface morphology of the optical glass sample after polishing using the polishing head prepared in Comparative Example 1.
[0062] from Figure 3 and 4 It can be seen that before polishing with the polishing head prepared in Example 1, the surface roughness RMS of the optical glass sample is between 0.606-0.753nm, and after polishing, the surface roughness RMS of the optical glass sample is between 0.0492-0.0566nm, the roughness is significantly reduced, and no obvious pits and other damages are observed on the surface; before polishing with the polishing head prepared in Comparative Example 1, the surface roughness RMS of the optical glass sample is between 0.532-0.784nm, and after polishing, the surface roughness RMS of the optical glass sample is between 0.336-0.448nm, although the roughness is slightly reduced, it can be clearly observed that the surface is uneven and there are scratches and damages, and the surface quality is not significantly improved. It can be seen that the polishing head with metal nano-molybdenum powder added has a better polishing effect, which further illustrates that the polishing head (polishing disc) prepared in Example 1 of the present application has a significant polishing effect on optical glass.
[0063] Test Example 2
[0064] In this test example, the polishing heads prepared in Example 2 and Comparative Example 2 were used to polish the optical glass samples, and the morphological changes of the optical glass sample surfaces before and after polishing were observed by atomic force microscopy. The polishing process was the same as that in Test Example 1 and will not be described in detail. The morphology of the polishing disc on the polishing head prepared in Example 2 was observed by atomic force microscopy. Figure 5As shown in (a), it can be seen that the metal nanoparticles are evenly distributed on the polishing surface of the polishing disc and exposed on the polishing surface. The sum of the cross-sectional areas of the metal nanoparticles protruding from the polishing surface at the same height as the polishing surface is 5.6% of the polishing surface area. The morphology of the optical glass sample polished using the polishing head prepared in Example 2 was observed using an atomic force microscope. The results are shown in FIG. Figure 5 As shown in (b) and (c). Figure 5 (b) is the optical glass sample before polishing. Figure 5 (c) is a polished optical glass sample. Figure 5 It can be seen from (b) and (c) that before the optical glass sample is polished using the polishing head prepared in Example 2, the RMS roughness of the optical glass sample is 0.361 nm, and after the polishing, the RMS roughness of the optical glass sample is 0.065 nm. It can be seen that after the optical glass sample is polished using the polishing head prepared in Example 2, the roughness of the optical glass sample is significantly reduced, and no obvious pits or other damage are observed on the surface.
[0065] The morphology of the polishing disk on the polishing head prepared in Comparative Example 2 was observed using an atomic force microscope. Figure 6 As shown in (a), only a small number of metal nanoparticles can be seen distributed on the polishing surface of the polishing disk, and the exposure degree is significantly lower than that of the polishing head prepared in Example 2. The morphology of the optical glass sample polished by the polishing head prepared in Comparative Example 2 was observed using an atomic force microscope. The results are as follows: Figure 6 As shown in (b) and (c). Figure 6 (b) is the optical glass sample before polishing. Figure 6 (c) is a polished optical glass sample. Figure 6 It can be seen from (b) and (c) that before the optical glass sample was polished using the polishing head prepared in Comparative Example 2, the RMS roughness of the optical glass sample was 0.427 nm, and after the polishing, the RMS roughness of the optical glass sample was 0.227 nm. After the optical glass sample was polished using the polishing head prepared in Comparative Example 2, the roughness of the optical glass sample did not decrease significantly, and obvious pits were observed on the surface.
[0066] Combining Test Example 1 and Test Example 2, it can be illustrated that the polishing disc prepared in the present application has an excellent polishing effect on optical glass samples by controlling the exposure degree of metal nanoparticles.
[0067] In summary, the polishing disc of the present application embeds metal nanoparticles in a hot-melt material layer, and the metal nanoparticles are evenly distributed on the polishing surface of the polishing disc and partially exposed on the polishing surface. By selecting the hot-melt material and controlling the exposure degree of the metal nanoparticles, the polishing disc has a good polishing effect, and the polishing disc of the present application does not need to add abrasive particles during the polishing process, will not damage the surface of the component to be polished, and can achieve polishing of a sub-angstrom level surface roughness.
[0068] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to this application.
Claims
1. A method for preparing a polishing disc, characterized in that: The polishing disc comprises a hot-melt material layer and metal nanoparticles embedded in the hot-melt material layer, wherein the metal nanoparticles are evenly distributed on the polishing surface of the polishing disc and partially exposed on the polishing surface; The metal nanoparticles include at least one of a metal element and a metal alloy; the metal element is one of titanium, chromium, iron, cobalt, nickel, molybdenum, palladium, tantalum, and platinum; the metal alloy is a combination of at least two of titanium, chromium, iron, cobalt, nickel, molybdenum, palladium, tantalum, and platinum; The metal nanoparticles protrude from the polishing surface, and the height of the metal nanoparticles protruding from the polishing surface is not less than 5% of the particle size of the metal nanoparticles; the sum of the cross-sectional areas of the parts of the metal nanoparticles protruding from the polishing surface at the same height as the polishing surface is not less than 5% of the area of the polishing surface; The preparation method of the polishing disc comprises the steps of: Providing hot melt materials and metal nanoparticles; The hot melt material is heated to a molten state, the metal nanoparticles are added, and the mixture is mixed to obtain a polishing disk precursor; Transferring the polishing disc precursor to a mold, applying a constant magnetic field to a side of the mold away from the outlet, and subjecting the mold to a temperature reduction treatment to obtain the polishing disc; The range of the constant magnetic field is larger than the area of the polishing disc, and the magnetic field strength of the constant magnetic field is not less than 10 T. Under the combined action of the magnetic field and the mold, the metal nanoparticles are partially exposed on the polishing surface.
2. The method for preparing a polishing disc according to claim 1, characterized in that: The hot-melt material is at least one of asphalt, rubber and silica sol.
3. The method for preparing a polishing disc according to claim 2, characterized in that: When the hot-melt material is asphalt, the needle penetration of the asphalt is 77-80 mm; when the hot-melt material is silica sol, the Shore hardness of the silica sol is 20-40 degrees.
4. A polishing disc prepared by the method for preparing a polishing disc according to any one of claims 1 to 3.
5. Use of the polishing disc according to claim 4 in the preparation of semiconductor components or components used for optical windows, wherein the polishing disc is used to polish semiconductor components or components used for optical windows.
6. The use according to claim 5, characterized in that: The method of using the polishing disc to polish semiconductor components or components applied to optical windows comprises: adding polishing liquid to the surface of the semiconductor components to be polished or the components applied to the optical window, and using the polishing disc to polish the semiconductor components to be polished or the components applied to the optical window; The polishing liquid includes an ionic liquid with a pH value less than 10.
Citation Information
Patent Citations
Chemical-mechanical planarization polishing pad for super-hard materials and preparation and polishing method
CN103252710A
Chemical mechanical polishing conditioner with optimal abrasive exposing rate
US20150202735A1